Design and Build a Web-Based Sumberagung Village Information System Using Php and Sql - Jiwandono, Tri Hardiyanto; Izzuddin, Ahmad; Hikmah, Nuzul (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2022)
The  Probolinggo  Regency  Government  encourages  every  village  to  have  a  website  page  to  makeit easier for the community to know broadly about programs and activities, as well as budget realization within the village  government.  In  addition,  the existence  of a  website can  be  used  to  promote the  potential  of the  village. Although  so  far  not  all  villages  in  Probolinggo  Regency  have  a  website,  but  for  villages  that  already  have internet  network  access,  it  is  an  obligation  to  have  a  website  as  a  means  of  sharing  information  with  the community. The purpose of this research is to design and build a system that can help the community to know the news,  programs  and data  of  Sumberagung village.  This village  information  system  uses  the  PHP  programming language and SQL database that can make it easier for the community to get information related to the village and  improve  the  quality  and  efficiency  of  community  services.  This  research  was  conducted  inseveral  stages, namely  the  design  of  software  using  flow  charts  or  called  flowchats  and  software  development  using  the waterfall model. From the results of the overall analysis of the tests carried out will determine the feasibility of the  system  features  that  have  been  made.  Feature -System  features  are  considered  feasible  if  the  overall  test results are in accordance with the expected output. And in the tests that have been carried out by this research based  on  the  Black  Box  test  table  above,  it  can  be  concluded  that  the  features  of  the  system  built  by  the researcher can be concluded that these features have been running well and according to needs.